2018
DOI: 10.33607/bjshs.v1i108.4
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Physical Fitness and Academic Achievements of Primary School Children

Abstract: Background.The purpose of this study is to estimate physical activity, physical fitness and assessment of mathematical achievements in primary schoolchildren. Methods. The study involved 1st grade students (N = 93), 45 of which were girls and 48 were boys. The flexibility test, the long jump test, 3 × 10 m speed shuttle run test, a medical (stuffed) 1 kg ball pushing from the chest test were used. Physical activity was measured using Children’s Physical Activity Questionnaire. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The learning achievements listed in the General Programs (Basic curriculum for primary education, 2016) in the field of geometry, measures, and measurement are incorporated into the diagnostic assessment program and described in the curriculum content. There are seven possible MDPT tasks [28].…”
mentioning
confidence: 99%
“…The learning achievements listed in the General Programs (Basic curriculum for primary education, 2016) in the field of geometry, measures, and measurement are incorporated into the diagnostic assessment program and described in the curriculum content. There are seven possible MDPT tasks [28].…”
mentioning
confidence: 99%
“…Finding suggests that promoting physical activity through game equipment provision during recess periods can contribute to reach the daily activity levels recommended for good health (Stefanie et al, 2006). Kliziene et al (2018) found that both boys and girls were physically active in physical education lessons (p > 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…On the sit-up test, girls in the specialist-led condition improved more than those in the control condition. Kliziene et al (2018) found that long jump results ranged from 105.2 cm (girls) to 118.3 cm (boys), statistically significant differences were detected (p < 0.05) The best score of the girls' shuttle running 3 × 10 m was 9.55 s, for boys it was 9.2 s, the worst performance time for boys was 13.68 s, for girls -13.54 s (p < .05).…”
Section: Discussionmentioning
confidence: 99%